Effects of a novel phosphodiesterase 10A inhibitor in non-human primates: A therapeutic approach for schizophrenia with improved side effect profile. (November 2016) - Masilamoni, Gunasingh J.; Uthayathas, Subramanian; Koenig, Gerhard; Leventhal, Liza; Papa, Stella M.
Abstract: Schizophrenia symptoms are associated with alterations in basal ganglia-cortical networks that include the cyclic nucleotides (cAMP/cGMP) signaling pathways. Phosphodiesterase 10A (PDE10A) inhibitors have been considered as therapeutic agents for schizophrenia because the regulation of cAMP and cGMP in the striatum by PDE10A plays an important role in the signaling mechanisms of the striatal-cortical network, and thereby in cognitive function. In the present study we assessed in non-human primates (NHPs) the effects of a novel PDE10A inhibitor (FRM-6308) that has demonstrated high potency and selectivity for human recombinant PDE10A in vitro. The behavioral effects of FRM-6308 in a dose range were determined in rhesus monkeys using a standardized motor disability scale for primates, motor tasks, and the "drug effects on the nervous system" (DENS) scale. The neuronal metabolic effects of FRM-6308 were determined with [(18)F]-fluorodeoxyglucose PET imaging. Results showed that FRM-6308 did not have any specific effects on the motor system at s.c. doses up to 0.32 mg/kg in NHPs, which induced a significant increase in the FDG-SUV in striatum (F 16.069, p < 0.05) and cortical (F 15.181, p < 0.05) regions. Higher doses induced sedation and occasional involuntary movements with clear development of tolerance after repeated exposures. These findings suggest that FRM-6308 has the adequate pharmacological profile to advance testing in clinical trials and demonstrate antipsychotic efficacy of PDE10A inhibition for the treatment of schizophrenia patients. Highlights: A new PDE10A inhibitor is profiled in primates as a candidate for antipsychotic therapy. FRM-6308 is highly selective and potent for PDE10A, and has good PK profile. FRM 6308 induced only mild sedation and dyskinesia at the highest dose tested (1 mg/kg). A range of (s.c.) doses of FRM-6308 has shown excellent tolerability in the primate. Non-sedative doses of FRM 6308 increased the striatal activity as measured by FDG-PET.